Ultrasonograpic Assessment of Relationship Between the Palmaris Longus Tendon and the Flexor Retinacular Ligament and the Palmar Aponeurosis of the Hand - Ertem K.; Siğirci A.; Karaca S.; Siğirci A.; Karakoç Y.; Yoloğlu S. (Tip Arastirmalari Dernegi, 2010)
Malatya, TurkeyAim: This study aimed to evaluate the presence of the Palmaris Longus Tendon (PLT) and the relationship between the Flexor Retinacular Ligament (FRL) and the Palmar Aponeurosis (PA) of the hand. Method: 62 voluntary subjects (31 female, 31 male students and personnel from the Inonu University, at the average age 28.38 ± 6.86 years ranging from 19 to 48 years) took part in this study using ultrasound. Result: Significant differences were found in the PA p-m-d diameters of subjects between with and without PLT bilaterally, on the right and the left hand (p<0.05), whereas there was no meaningful difference considering FRL diameters (p>0.05). Furthermore, this ultrasonographic assessment revealed the continuity of collagen bunches of the PL tendon up to FRL, but not PA. Conclusion: Although not demonstrated by ultrasonography here, the increased thickness of the PA in subjects with a PLT supports the findings in the literature in which the structural continuity between the PLT and PA have been stressed.
Palmaris longus tendon varlığı ile eldeki flexor retinacüler ligaman ve palmar aponöroz arasındaki ilişkinin USG ile değerlendirilmesi
Keywords: Flexor Retinacular Ligament; Palmar Aponeurosis; Palmaris Longus Tendon; Ultrasonography